Strategi Kepala Sekolah Dalam Pelaksanaan Pedidikan Inklusif Di SMKN 1 Cikalongkulon Cianjur - Dewiana, Ratih; Siswanto, Romi; Rahmat, Rahmat (Program Studi Pendidikan Agama Islam, 2023)
This research aims to examine the principal's strategy in implementing inclusive education at SMKN 1 Cikalongkulon Cianjur, as well as identifying supporting and inhibiting factors. A qualitative approach was used in this research with a case study method. Data collection was carried out through interviews, observation and documentation studies. The research results show that school principals apply various strategies in the aspects of accepting new students, student placement, curriculum, learning settings, learning approaches, learning evaluation, funding, and special service management. These strategies are in line with the concept of inclusive educational leadership and the principles of Inclusive Education. Supporting factors for implementing inclusive education include the attitude of acceptance by the school community, cooperation with stakeholders, availability of committee funds, flexible curriculum, adequate infrastructure and comprehensive counseling services. Meanwhile, the inhibiting factors are the absence of special supervising teachers and the lack of support from the Provincial Education Office and the Ministry of Education and Culture. Despite this, school enthusiasm and efforts to develop inclusive education remain high. The success of inclusive education requires commitment and cooperation from all parties.